Testantidiabetic activity of a combination of 70% ethanol extract of meniran leaves (Phyllanthus Niruri L.) and glibenclamide in male white Wistar rats induced by alloxan - Azzahra, Annisa Alya; Sujono, Tanti Azizah (Institute of Computer Science (IOCS), 2024)
Diabetes mellitus is a metabolic disease that causes hyperglycemia due to impaired insulin function (insulin resistance). The use of glibenclamide has side effects in the form of hypoglycemic and weight gain. This study aims to determine the activity of a combination of 70% ethanol extract of meniran leaves (EEDM) and glibenclamide in reducing blood glucose and body weight of rats against the use of single glibenclamide. A completely randomized design method was used involving 28 rats divided into 7 groups. Normal control (KN) was given distilled water; negative control (K(-)) was given distilled water; positive control (K(+)) was given glibenclamide 1 mg/kgBW, EEDM treatment group doses of 5; 10; 20 mg/kgBB and a combination group of glibenclamide and EEDM 5 mg/kgBB. Alloxan 150 mg/kgBW intraperitoneally (ip) and 30% glucose solution orally were used to induce the hyperglycemic rat model. Blood sugar levels and body weight were checked on days: 0, 7, 14 after treatment. Based on the results of statistical tests showed that EEDM all doses and combinations have antidiabetic activity (p<0.05). The use of a combination of glibenclamide 1 mg/kgBB and ethanol extract of meniran leaves 5 mg/kgBB can also overcome the side effects of weight gain from the use of glibenclamide alone.